The Impact and Implication of Peripheral Vascular Leakage on Ultra-Widefield Fluorescein Angiography in Uveitis. (3rd April 2019) - Thomas, Akshay S.; Redd, Travis; Campbell, John P.; Palejwala, Neal V.; Baynham, Justin T.; Suhler, Eric B.; Rosenbaum, James T.; Lin, Phoebe
ABSTRACT: Purpose : To study if peripheral vascular leakage (PVL) on ultra-widefield fluorescein angiography (UWFFA) prognosticates complications of uveitis or necessitates treatment augmentation. Methods : Retrospective cohort study of uveitis patients imaged with UWFFA and ≥1 yr of follow-up. Results : We included 73 eyes of 42 patients with uveitis. There was no difference in baseline, intermediate, final visual acuity ( p = 0.47–0.95) or rates of cystoid macular edema (CME) ( p = 0.37–0.87) in eyes with PVL vs. those without. Eyes with PVL receiving baseline treatment augmentation were more likely to have baseline CME but were not more likely to have impaired visual acuity at final follow-up. PVL was independently associated with treatment augmentation on generalized estimating equation analysis with multivariable linear regression (OR: 4.39, p = 0.015). Conclusions : PVL did not confer an increased risk of impaired VA or CME at ≥1 yr follow-up but was possibly an independent driver of treatment augmentation.